Edukacja mniejszości romskiej w Polsce - Przybyszewska, Dominika (Kultura-Społeczeństwo-Edukacja, 2014)
The Roma people make one of the ethnic minorities recognized in Poland. In comparison in education which is based on continuation of their tradition, the Roma education aims at making the transmission of Polish culture more easy. In Poland in the years 2004-2013 the "Programme for the Roma communities". Its most important element was education which makes a sort of challenge. The teacher has to organize the learning process in order to overcome many obstacles. It is necessary to motivate the pupils to work, to integrate the class despite the existing cultural differences, including the initiating cooperation with parents. Gaining trust of the Roma milieu is one of the most important elements having influence on the success of the enterprise of education of children coming from those minorities. It is also important to diminish the social distance of Poles towards them and to getting rid of prejudice and fighting existing stereotypes.